Cost of tobacco-related diseases, including passive smoking, in Hong Kong. Issue 2 (24th March 2006) - McGhee, S M; Ho, L M; Lapsley, H M; Chau, J; Cheung, W L; Ho, S Y; Pow, M; Lam, T H; Hedley, A J
Abstract : Background: Costs of tobacco-related disease can be useful evidence to support tobacco control. In Hong Kong we now have locally derived data on the risks of smoking, including passive smoking. Aim: To estimate the health-related costs of tobacco from both active and passive smoking. Methods: Using local data, we estimated active and passive smoking-attributable mortality, hospital admissions, outpatient, emergency and general practitioner visits for adults and children, use of nursing homes and domestic help, time lost from work due to illness and premature mortality in the productive years. Morbidity risk data were used where possible but otherwise estimates based on mortality risks were used. Utilisation was valued at unit costs or from survey data. Work time lost was valued at the median wage and an additional costing included a value of US1.3 million for a life lost. Results: In the Hong Kong population of 6.5 million in 1998, the annual value of direct medical costs, long term care and productivity loss was US532 million for active smoking and US156 million for passive smoking; passive smoking accounted for 23% of the total costs. Adding the value of attributable lives lost brought the annual cost to US9.4 billion. Conclusion: The health costs of tobacco use are high and represent a net loss to society. Passive smoking increases these costs by at least a quarter. This quantification of the costs of tobacco provides strong motivation for legislative action on smoke-free areas in the Asia Pacific Region and elsewhere.